A Qualitative Study of the Impact of Education on Community Welfare: Prosperous Family Card Services - Faizah , Andi Nurul; Perawati, Perawati (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study intends to determine the effect of education on the Family Welfare Card Service and to determine the other factors besides education that influence the Family Welfare Card service. This study employs a descriptive qualitative research design. This research focuses on individuals from diverse educational backgrounds residing in Mangempang Village, Barru District, and Barru Regency. The research uses observation, interviews, and documentation as data collection techniques. The data analysis used is an interactive qualitative analysis model, including the stages of data collection, presentation, and drawing conclusions. The results of this study indicate that the level of community education has a positive impact on the Family Welfare Card service in Mangempang Village, Barru District, Barru Regency; each beneficiary family has different levels of satisfaction related to the Family Welfare Card service depending on the good or negative aspects of their experience as KKS recipients. Beneficiary families feel that the services provided by the government in this KKS program are satisfactory and the assistance can meet the needs of the beneficiary community. Additionally, the Family Welfare Card Program service is influenced by two factors: supporting factors and inhibiting factors. Supporting factors include the community's enthusiasm for socialization and the effective coordination among the involved officers. On the other hand, inhibiting factors include a lack of knowledge about access to aid recipients, inconsistent and inaccurate KKS recipient data, limited human resources, low public understanding, and social jealousy due to low levels of education in the community.